Constraint-Based Sound-Motion Objects in Music Performance - Godøy, Rolf Inge (Frontiers in Psychology, 2021)
The aim of this paper is to present principles of constraint-based sound-motion objects in music performance. Sound-motion objects are multimodal fragments of combined sound and sound-producing body motion, usually in the duration range of just a few seconds, and conceived, produced, and perceived as intrinsically coherent units. Sound-motion objects have a privileged role as building blocks in music because of their duration, coherence, and salient features, and emerge from combined instrumental, biomechanical, and motor control constraints at work in performance. Exploring these constraints and the crucial role of the sound-motion objects, can enhance our understanding of generative processes in music and have practical applications in performance, improvisation, and composition.